Stick Man - Donaldson, Julia; Scheffler, Axel (New York : Arthur A. Levine Books, 2009)
Stick Man ends up far away from his family tree when he is fetched by a dog, thrown by a child, used as a snowman's arm, and even put on a fire, but finally Santa Claus steps in to make sure that Stick Man and his family have a joyous Christmas.
1.8
K-3
Keywords: Christmas -- Fiction; Santa Claus -- Fiction; Stories in rhyme; Twigs -- Fiction; Christmas -- Fiction; Santa Claus -- Fiction; Stories in rhyme; Twigs -- Fiction; Picture books for children